2019
DOI: 10.1001/jamanetworkopen.2018.7896
|View full text |Cite
|
Sign up to set email alerts
|

Association of Nonsteroidal Anti-inflammatory Drug Prescriptions With Kidney Disease Among Active Young and Middle-aged Adults

Abstract: Key Points Question What is the association between prescribed dosages of nonsteroidal anti-inflammatory drugs and later incident kidney disease among active young and middle-aged adults? Findings In this cohort study of 764 228 US Army soldiers, prescriptions of more than 7 daily defined doses of nonsteroidal anti-inflammatory drugs per month were associated with modest but significant increases in the adjusted hazard ratios of acute and chronic kidney dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 41 publications
1
35
1
1
Order By: Relevance
“…Because we do not have genetic data in our database, we are unable to control for population substructure. However, the magnitude of the SCT effect we observed in this study is approximately as large as the entire difference between African American soldiers and white soldiers in our dataset (Nelson et al , ), so a small shift in ancestry proportions would not be enough to drive the entire observed effect.…”
Section: Discussioncontrasting
confidence: 60%
“…Because we do not have genetic data in our database, we are unable to control for population substructure. However, the magnitude of the SCT effect we observed in this study is approximately as large as the entire difference between African American soldiers and white soldiers in our dataset (Nelson et al , ), so a small shift in ancestry proportions would not be enough to drive the entire observed effect.…”
Section: Discussioncontrasting
confidence: 60%
“…86 A retrospective longitudinal cohort study of US Army soldiers without pre-existing kidney disease demonstrated 20% greater risk for CKD progression among patients receiving more than 7 World Health Organization-defined daily doses per month of total NSAIDs compared with nonusers. 87 Similarly, a casecontrol study found an association between stage 5 CKD development and NSAIDs only in users of the highest quantities. 79 In summary, although the risk for CKD progression due to NSAID use is not insignificant, it appears to be small, related to cumulative dose, and modifiable by appropriate patient selection in patients with mild to moderate CKD.…”
Section: Hypertensionmentioning
confidence: 96%
“…A self-reported study of over-the-counter and prescribed use of ibuprofen, which falls into the class of NSAIDs, noted that 90% took it regularly. In comparison, 37% took other forms of NSAIDs in addition to ibuprofen, and 11% exceeded the daily recommended limit of ibuprofen [2]. This case report emphasizes the importance of public awareness regarding analgesics and its associated side effects with large doses.…”
Section: Introductionmentioning
confidence: 83%